Rorty’s Philosophy and the mirror of Rhetoric - Marín- Casanova, José A. (Pensamiento. Revista de Investigación e Información Filosófica, 2014)
Rhetoric is not a special issue in Rorty’s work. In fact, there is not rortian Philosophy of Rhetoricin the objective sense of the genitive. However, when breaking explicitly «the mirror of nature», Rorty is implicitly breaking with the condition that makes possible the divorce between Philosophy and Rhetoric.This article aims to make explicit that implicit matter, and shows Rorty’s Philosophy as a Philosophy of Rhetoric in the subjective sense of the genitive, i.e., as a Rhetoric of Philosophy or a Rhetorical Philosophy.